2011
DOI: 10.1590/s0103-50532011000700013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from roots of Colubrina greggii var. yucatanensis and evaluation of their antiprotozoan, cytotoxic and antiproliferative activities

Abstract: A purificação do extrato da raiz de Colubrina greggii var. yucatanensis levou ao isolamento e identificação do ácido 3-O-acetil ceanótico, um novo triterpeno natural, juntamente com os metabólitos já descritos: ácido ceanótico, ácido cenoténico, ácido betulínico, discarina B e crisofaneína. Os produtos naturais e os derivados semi-sintéticos éster de acetil dimetil ceanotato, dimetil ceanotato e peracetato de crisofaneína mostraram moderada a baixa atividade leishmanicida e tripanocida. Nenhum dos metabólitos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…(Rhamnaceae), a shrub used for the treatment of liver diseases, ulcerations, and tuberculosis in Mayan traditional medicine. 62 The natural ceanothanes and some synthetic derivatives showed moderate leishmanicidal and trypanocidal activities when tested against Leishmania amazonensis and Trypanosoma cruzi var. tulahuen, respectively.…”
Section: ■ Screening the Mayan Pharmacopeiamentioning
confidence: 99%
See 2 more Smart Citations
“…(Rhamnaceae), a shrub used for the treatment of liver diseases, ulcerations, and tuberculosis in Mayan traditional medicine. 62 The natural ceanothanes and some synthetic derivatives showed moderate leishmanicidal and trypanocidal activities when tested against Leishmania amazonensis and Trypanosoma cruzi var. tulahuen, respectively.…”
Section: ■ Screening the Mayan Pharmacopeiamentioning
confidence: 99%
“…tulahuen. 62 A different class of metabolites, the benzochromenes (6,6dimethyl-2-methoxy-6H-benzo[c]chromen-9-yl)methanol (108) and 2-methoxy-6,6-dimethyl-6H-benzo[c]chromen-9carbaldehyde (109), isolated from the root extract of Bourreria pulchra Millsp. (Boraginaceae), a medicinal plant with DNAinteracting activity, also exhibited antiprotozoal properties, with 108 being particularly active against L. mexicana and T. cruzi.…”
Section: ■ Screening the Mayan Pharmacopeiamentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other studies have also reported the antimalarial potential of that compound and its derivatives. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] A few tetracyclic diterpenes have also shown antimalarial properties. One example is a norpimaran lactone (1d, Figure 1) obtained from manool, 21 and another is kaurenoic acid (3a, Figure 3) described as weakly active.…”
Section: Introductionmentioning
confidence: 99%